Answer:
C
Explanation:
We start with the second line;
3x -2y + 4 = 0
3x + 4 = 2y
divide through by 2
3x/2 + 2 = y
Comparing this with standard form of y = mx + c
where m is slope
This means 3/2 is slope of the line
Since this line is perpendicular to the other line, then the product of their slopes is -1
3/2 * slope of second line = -1
Slope of second line = -1 divided by 3/2 = -2/3
We use the point slope form to find the equation of the other line
y-y1 = m(x-x1)
where m = -2/3 and (x1,y1) = (2,-3)
y-(-3) = -2/3 (x-2)
y + 3 = -2/3 (x -2)
3(y + 3) = -2(x-2)
3y + 9 = -2x + 4
3y + 5 = -2x
3y + 2x + 5 = 0